2020
DOI: 10.3389/fpsyg.2020.01552
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Executive Functions for Motor Performance in Preschool Children as Compared to Young Adults

Abstract: Evidence suggests that executive and motor functions are functionally intertwined, with the interrelation between the two processes influenced by the developmental stage of the individual. This study examined executive and motor functions in preschool children (n = 41; 65-83 months), and investigated if, and how, preschoolers cognitive-motor functioning differs from that of young adults (n = 40; 18-31 years), who served as a control group reflecting the upper bound of cognitive-motor development. As expected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 78 publications
2
33
0
Order By: Relevance
“…Specifically, Stuhr et al (2020) found moderate to strong associations between working memory and three motor functions (strength, speed, and manual dexterity) in preschool children, but no significant associations between any measured cognitive and motor functions in young adults. Additionally, Stuhr et al (2020) reported that working memory explained unique portions of preschool children’s speed and manual dexterity. Furthering this line of research, van der Fels et al (2015) proposed that the connection between sensorimotor functions and EFs are stronger in childhood than in adolescence because of the changes in the developmental rate of these functions.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Specifically, Stuhr et al (2020) found moderate to strong associations between working memory and three motor functions (strength, speed, and manual dexterity) in preschool children, but no significant associations between any measured cognitive and motor functions in young adults. Additionally, Stuhr et al (2020) reported that working memory explained unique portions of preschool children’s speed and manual dexterity. Furthering this line of research, van der Fels et al (2015) proposed that the connection between sensorimotor functions and EFs are stronger in childhood than in adolescence because of the changes in the developmental rate of these functions.…”
Section: Introductionmentioning
confidence: 84%
“…The similar protracted developmental timelines of specific sensorimotor functions and EFs suggest that there are interrelations between these functions. Findings from recent studies ( Roebers and Kauer, 2009 ; Weigelt et al, 2009 ; Stöckel and Hughes, 2016 ; Stöckel et al, 2017 ; Oberer et al, 2018 ; Stuhr et al, 2020 ), have indicated that sensorimotor functions and EFs are inherently intertwined. For example, Weigelt et al (2009) found a link between working memory and perceptual-motor performance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations